Discussing about "Inclusion in Sharing-Based Services". A design workshop using an analytic tool. (28th July 2017) - Busciantella Ricci, Daniele; Dong, Hua; Rinaldi, Alessandra; Tosi, Francesca
Abstract: The activities based on collaboration and shared consumption are hard to classify and it is not possible to define a taxonomy. Also, in this field some evidence address racial discriminations, the lack of worker protections and a lack of regulations. The authors argue that considerations about 'inclusion' and 'exclusion' state are needed for services involved in sharing-based activities. In addition, the 'Sharing-Based Services' (SBS) conceptual framework is proposed to study and analyse services in sharing-based contexts. In particular, this paper describes the activities of a design workshop organised with the aim to open a discussion about the aspects of the 'inclusion' and 'exclusion' in SBS. An analytic toolkit ('Sharinc') was used with the aim to consider these aspects analysing the structure of a SBS. Finally, this paper presents the results of the workshop achieved by the usage of the toolkit and by participants' feedback.